Mapping Of Dominant Sub Sectors And Creative Economic Growth In Palopo City 2021 To 2022 - palinoan, hendra safri (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This research aims to maping the creative economy sub-sector in Palopo City in 2021-2022 as a basis for the regional government to issue policies related to improving the local economy, the main aim is to find out how business growth and creative economy mapping in Palopo City are and to find out the dominant sub-sectors to be developed in Palopo City, the research method used to answer these objectives used a qualitative research design by interviewing 65 informants who were creative economy actors in Palopo City spread across nine sub-districts, then measured using qualitative data analysis, namely data reduction, data presentation, and withdrawal. Conclusion: The results of the research are that the growth of the creative economy in Palopo City over the last year has increased in line with the new normal conditions after the Covid 19 pandemic and the dominant sub-sector of the creative economy in Palopo City is culinary with a presentation of 76.9%, while 23.1% dominated by 9 other sub-sectors, and based on regional mapping, Wara sub-district and Tompotika sub-district have many creative economic actors.Keywords : Mapping, Creative Economy, Economic Growth.